Implikasi Yuridis Perjanjian Perkawinan yang Didaftarkan Pada Saat Proses Perceraian - Delia Astrid Zahara; Antarin Prasanthi Sigit (LPPM Universitas Ekasakti Padang, 2023)
A marriage agreement made by a husband and wife before or during the marriage is binding on both parties who have promised since the marriage took place unless otherwise stated in the marriage agreement. In order for a marriage agreement to be binding on third parties involved in the marriage agreement, the marriage agreement must be recorded by a marriage registrar. The marriage agreement should be immediately registered with the marriage registrar to fulfill the principle of publicity. However, in reality, many married couples do not immediately register their marriage agreement with the marriage registrar, and there are even marriage agreements which are only registered with the marriage registrar when the divorce process is underway by only one of the parties. The aim of this research is to analyze whether there is good faith on the part of the party registering the marriage agreement with the marriage registrar employee when the divorce process is in progress as well as the legal consequences of the marriage agreement registered with the marriage registrar employee during the divorce process on joint property. The form of research used in this research is normative juridical, namely research that uses secondary data in the form of primary legal materials and secondary legal materials to analyze the problems raised in this research. The results of this research indicate that recording a marriage agreement with a marriage registrar during the divorce process by one party without the knowledge of the other party is evidence of a lack of good faith on the part of that party. Apart from that, the results were also obtained that the marriage agreement that had just been registered with the marriage registrar during the divorce process had no effect on the marital assets obtained by involving a third party and were obtained during the marriage, before the marriage agreement was recorded by the marriage registrar.